Analisis Faktor Teknis dalam Risiko Penyelenggaraan Proyek Bangunan Gedung Pemerintahan - Sitompul, Fauzi; Carlo, Nasfryzal; Zaitul, Zaitul (Universitas Negeri Gorontalo, 2025)
The construction industry faces high uncertainty due to economic fluctuations, regulatory changes, and resource limitations. In South Tapanuli, construction projects often experience delays, budget overruns, and quality issues due to economic factors. This study aims to identify the most dominant economic risks in building construction. Using AS/NZS 4360:2004 and the Relative Importance Index (RII), this research analyzes the impact of raw material price fluctuations, delayed payments, labor wage increases, and regulatory changes. Findings indicate that raw material price fluctuations (RII: 0.948) and delayed payments (RII: 0.934) are the highest risk factors. Financial risks pose major challenges, requiring effective mitigation strategies. Recommendations include stabilizing material prices, reforming payment systems, and improving labor wage management. Proper policy implementation can enhance efficiency and project sustainability in this region.